2010
DOI: 10.1111/j.1365-2850.2010.01642.x
|View full text |Cite
|
Sign up to set email alerts
|

Supporting mental health nurses to address the physical health needs of people with serious mental illness in acute inpatient care settings

Abstract: There is overwhelming evidence that the physical health needs of those with serious mental illness have been neglected by health service professionals. Mental health nurses (MHNs) could play a key role in meeting these needs particularly during hospital admissions, yet they are uncertain about their role, have variable levels of confidence and lack appropriate skills and training. This study investigated MHNs' views and practices of physical health management for adults receiving acute inpatient treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
183
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(192 citation statements)
references
References 6 publications
9
183
0
Order By: Relevance
“…MHCPs must fill in the required documents in a manner as regulated by the MHCA. [14] The treatment was appropriate if it was in keeping with treatment outlined by treatment guidelines generally accepted in clinical practice locally, e.g. based on the American Psychiatric Association Practice Guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MHCPs must fill in the required documents in a manner as regulated by the MHCA. [14] The treatment was appropriate if it was in keeping with treatment outlined by treatment guidelines generally accepted in clinical practice locally, e.g. based on the American Psychiatric Association Practice Guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…[12,13] These negative attitudes translate to poor clinical management of patients. Some patients are denied proper physical work-up, including history taking, physical examination and laboratory investigations, on the basis of being mentally ill. [14][15][16] The poor levels of care result in lack of detection of natural diseases and non-treatment. This in turn leads to a high rate of mortality from natural diseases in mentally ill people compared with the general population.…”
mentioning
confidence: 99%
“…For example, the learning disability nurses' collaboration in primary care has initiated annual health checks for adults with learning disabilities (Martin et al, 2004, Manthorpe andMartineau, 2010). Additionally, studies have shown that mental health nurses are in an ideal position to assess mental health service users' physical health needs (Nash, 2010a;Howard and Gamble 2011;Robson et al, 2012;Edward et al, 2012;). Sheerin (2012) suggests that to be truly holistic, learning disability nurses need to work with the service user to gain access to the same healthcare as the general population.…”
Section: The Learning Disability Nursing and Mental Health Nursing Rolementioning
confidence: 99%
“…Training needs analyses carried out by Nash (2009) and Howard and Gamble (2011) of in-patient and community-based mental health staff found that staff did not have up-to-date skills or knowledge, and lacked confidence in physical care activities; thus delaying appropriate intervention. Manthorpe and Martineau (2010) also noted that health and social care staff providing services for people with a learning disability need education and training in physical health interventions.…”
Section: The Learning Disability Nursing and Mental Health Nursing Rolementioning
confidence: 99%
See 1 more Smart Citation